2014
DOI: 10.3389/fimmu.2014.00006
|View full text |Cite
|
Sign up to set email alerts
|

B-1a B Cells Regulate T Cell Differentiation Associated with Pregnancy Disturbances

Abstract: During pregnancy, the maternal immune system faces a double dilemma: tolerate the growing semi-allogeneic fetus and at the same time protect the mother and the progeny against pathogens. This requires a fine and extremely regulated equilibrium between immune activation and tolerance. As professional antigen presenting cells, B cells and in particular B-1a B cells, can activate or tolerize T cells and thus participate in the generation or regulation of the immune response. B-1a B cells were involved in the humo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
1
30
2
3
Order By: Relevance
“…B cells can also be recruited by the chorioamniotic membranes [14] and constitute a portion of the choriodecidual leukocytes [16,57,58]. The role of B cells during pregnancy and its complications have been widely studied by Jensen and collaborators [59][60][61][62][63][64][65][66][67][68]. Taken together, these data provide further evidence that the adaptive limb of immunity is involved in the process of labor.…”
Section: Resultssupporting
confidence: 52%
“…B cells can also be recruited by the chorioamniotic membranes [14] and constitute a portion of the choriodecidual leukocytes [16,57,58]. The role of B cells during pregnancy and its complications have been widely studied by Jensen and collaborators [59][60][61][62][63][64][65][66][67][68]. Taken together, these data provide further evidence that the adaptive limb of immunity is involved in the process of labor.…”
Section: Resultssupporting
confidence: 52%
“…Therefore, the suppression of T cell cytokine production by PD-L2 in the context of the germinal center reaction may be unlikely. On the other hand, B-1a cells are known to promote Th1 and Th17 responses, although the ability to polarize Th1/Th17 differentiation has been reported to be independent of PD-L2 (103) since PD-L2 − and PD-L2 + B-1 cells have similar efficacy in eliciting differentiation (104, 105). Nonetheless, our work indicates further investigation into B-1 cell PD-L2–mediated regulation of cytokine production is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…27 Research has indicated that downregulation of Th17 cells and maintaining the balance between Th17 and Treg is beneficial to maintaining immune balance of the maternal-fetal interface. 28 Furthermore, we detected the levels of Th1 (IFN-γ), Th2 (IL-10) and Th17 (IL-17) in placental tissue and serum. The secretion of IL-10 mRNA and protein was reduced in decidual tissues of the abortion group, which exhibited increased secretion of IFN-γ mRNA and protein compared with the normal pregnancy control groups.…”
mentioning
confidence: 99%